2019
DOI: 10.21203/rs.2.9211/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intensive Phase Treatment Outcome and Associated Factors among Patients Treated for Multi Drug Resistant Tuberculosis in Ethiopia: A retrospective cohort study

Abstract: Background Multi-drug resistant Tuberculosis (MDRTB) is a strain of Mycobacterium tuberculosis that is resistant to at least Rifampicin and Isoniazid drugs. The treatment success rate for MDRTB cases is lower than for drug susceptible TB. Monitoring the early treatment outcome and better understanding the specific reasons for early unfavorable treatment outcome are important to evaluate the effectiveness of tuberculosis control and preventing the emergence of extremely drug resistant tuberculosis. However, th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Then, 347 articles were screened by title and abstract. The full-text screening was conducted for 58 articles, and 17 articles that fulfilled the eligibility criteria were included in the final analysis (Ketema et al, 2019;Molie et al, 2019;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019;Tola et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018;Tulu and Kahissay, 2014) (Table 1 and Figure 1). All of the studies were hospital-based retrospective cohort studies conducted among patients with DR-TB treated under TICs found in different parts of the country.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, 347 articles were screened by title and abstract. The full-text screening was conducted for 58 articles, and 17 articles that fulfilled the eligibility criteria were included in the final analysis (Ketema et al, 2019;Molie et al, 2019;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019;Tola et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018;Tulu and Kahissay, 2014) (Table 1 and Figure 1). All of the studies were hospital-based retrospective cohort studies conducted among patients with DR-TB treated under TICs found in different parts of the country.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Additionally, the clinical profiles (comorbidity types, clinical complication types, anatomical site of infection, diagnostic methods, drug resistance profiles, HIV serostatus, treatment outcomes and definition of anemia) of DR-TB patients per individual study were assessed and we summarized this in detail in Table 2. Among all 17 studies, 12 (Alene et al, 2017;Woldeyohannes et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018) and 15 (Ketema et al, 2019;Molie et al, 2019;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019;Meressa et al, 2015;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;Molalign and Wencheko, 2015;Woya et al, 2019;Abebe et al, 2020;Baye et al, 2018) studies explored mortality and poor treatment outcomes, respectively. The incidence density rate of poor treatment outcome and mortality using the time to an event (poor treatment outcome or mortality) were explored by 12 (Ketema et al, 2019;Alene et al, 2017;Limenih and Workie, 2019;Woldeyohannes et al, 2019;Getachew et al, 2013;Girum et al, 2017;Shimbre et al, 2020;Gebre et al, 2020;Fantaw et al, 2018;<...>…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, all patients in the same group received the same regimen as per national guidance and widely approached in Ethiopia [8,9]. The intensive phase of drug-resistant TB, the rst 8-12 months, is the period in which patients suffer from critical disease conditions and drug side effects [10,11]. Moreover, has life-threatening adverse drug effects of second-line anti-TB medications led to more frequent and prolonged hospitalizations during this phase of the treatment [12,13].…”
Section: Introductionmentioning
confidence: 99%